Process diversity in software development: an industrial study. Issue 4 (1st August 2019) - Utku, Semih; Şahin, Serra
Abstract : Software companies need to employ state‐of‐the‐art technologies to meet customer requirements. Owing to the complexity of contemporary software products and uncertainty concerning the budget for the required resources, companies use process‐oriented quality management techniques in order to guarantee appropriate product quality. In this light, standardised quality assurance system that uses the capability maturity model integration‐development (CMMI‐DEV) program are incorporated into software development processes, and software companies aim to enhance productivity by acquiring CMMI‐DEV certificates. In this study, an approach based on CMMI‐DEV is used to develop software process diversity for an international company. The results show that the proposed software process diversity model can be used to assess and improve processes in middle‐sized software companies that have identical technical frameworks and similar business structures.